Effects of dietary management and iron supplementation on protein energy malnutrition cases with anemia in the National Children's Hospital, Metro Manila - Malik, Mohammad Suhud
This study was conducted to determine the effect of dietary management with or without iron supplementation on the hemoglobin levels of anemic preschool children with protein-energy malnutrition in the Malnutrition Ward of the National Children's Hospital in Quezon City, Metro Manila. Anemia status was determined based on the hemoglobin and hematocrit levels using the Cyanmethemoglobin method and Guest-Weishelbam method, respectively. Hookworm status was determined by the direct/simple fecal smear technique. The study group was composed of 50 malnourished anemic children aged 6 to 71 months and found negative of hookworm infection. The subjects were randomly allocated into the control and experimental groups. The children in the control group received the 'Prescribed diet' (high calorie, high protein) alone, while the children in the experimental group received the 'prescribed diet' plus iron supplementation in 2 and 4 weeks' treatment. The servings of the 'prescribed diet' were weighed on standard dietetic scales with the aim of giving 100-200 kcal and 4-6 g protein per kg body weight (BW) per day computed from ideal BW. Ferrous sulfate as iron supplementation was orally given 1 hour after lunch to each patient in the experimental group in syrup form at a dose 6 mg of elemental iron per kg BW per day. Increasing hemoglobin and hematocrit were observed in both control and experimental groups during the duration of treatment. The mean increases in hemoglobin levels were 1.12 g and 2.7 g and the hematocrit levels were 3.88 vol and 10 vol after 2 weeks' and 4 weeks' treatment, respectively in the experimental group. On the other hand, for the control group the mean increase in hemoglobin values were 0.28 g and 0.51 g and the hematocrit levels were 1.32 vol and 2.43 vol after 2 and 4 weeks' treatment, respectively. It was observed that the hemoglobin and hematocrit values in the experimental group increased 4-5 times more than those in the control group at 2 and 4 weeks of treatment. The findings of the present study revealed that the 'prescribed diet' (high calorie, high protein) plus an optimum dose of iron supplementation was more effective in improving the hemoglobin levels of anemic children with protein-energy malnutrition within a period of 2 and 4 weeks' treatment compared with the group given the 'prescribed diet' only.